Preparation of biodiesel from oil palm industrial waste using sulphated heterogeneous catalyst - Nurul Hajar, Embong (2016)
The use of waste, particularly in the biodiesel industry has gained great potential in countering higher feedstock cost. In the present work, methyl ester was prepared from waste sources, palm fatty acid distillate (PFAD) and decanter cake oil (Dc-oil) via solid acid catalysts (SO42-/TiO2-SiO2 and NiSO4/SiO2). In line with the costing related matter, silica from rice husk ash (RHA), an agricultural waste, is used as a support for all the catalysts. The SO42-/TiO2-SiO2 and NiSO4/SiO2 catalysts were prepared by wet impregnation method. The obtained results showed that, both prepared catalysts lay in acidic form as tested using Hammett indicators. Both of the catalysts possessed mesoporous structures which were ideal catalyst for biodiesel production. PFAD was successfully esterified using SO42-/TiO2-SiO2 (calcined at 500 ºC) under the optimal conditions of 2.97 wt.% catalyst amount, 5.85:1 methanol to PFAD molar ratio and reaction time of 3.12 h to produce 93.3% methyl ester. Similarly, 93% methyl ester was achieved using NiSO4/SiO2 (calcined at 300 ºC) under the optimal conditions of 15 wt.% catalyst amount, 5:1 methanol to PFAD molar ratio and 7 h of methanol refluxing process. As for Dc-oil, SO42-/TiO2-SiO2 was used to transesterify the oil at optimal conditions of 5 wt.% catalyst amount , 9:1 methanol Dc-oil molar ratio for 5 h response time, producing 60.7% methyl esters. Similarly, 71% methyl esters was achieved using NiSO4/SiO2 under the optimal conditions of 11 wt.% catalyst amount, 15:1 methanol to oil molar ratio for 9 h reaction time. The prepared SO42-/TiO2-SiO2 catalyst for the esterification of PFAD was found to be reused up to two times with more than 90% methyl esters produced. On other hand, NiSO4/SiO2 catalyst for the esterification of PFAD can be reused once only with methyl esters produced about 90%. Besides that, the findings also revealed SO42-/TiO2-SiO2 had better catalytic activity in esterification of PFAD and transesterification of Dc-oil compared to NiSO4/SiO2. The investigated solid acid catalysts, SO42-/TiO2-SiO2 and NiSO4/SiO2 were found applicable for esterification and transesterification of high FFA feedstock especially from waste feedstock.